Autologous tenocyte implantation into shoulder tendon pathology in an elite swimmer. (January 2018) - Schwab, Laura M.; Blanch, Peter; Young, Mark
Abstract: Introduction: The use of novel bioengineer treatment techniques such as Autologous Tenocyte Implantation (ATI) have shown promising improvements in both pain ratings and functional outcomes in elbow, gluteal and shoulder tendon pathology. This case will review the injury timeline of ATI intervention in an elite male swimmer with subscapularis tendon pathology and investigate whether ATI has a concomitant healing effect associated with improved functional outcomes. Methods: A palmaris longus tendon biopsy was performed and cells were expanded by in-vitro culture. Autologous tenocytes were injected into the subscapularis site identified. Three blinded radiologists reported on pre and post shoulder MRIs using the same 3T MRI protocol. A validated rating scale for severity of tendinopathy (0–3) and degree of tear (0–3) was used and hand-held Dynamometry (HHD) strength was recorded. Results: Independent blinded radiology review demonstrated a significant reduction in tear size and improved tendon morphology. IR strength on HHD returned to baseline strength levels post ATI (231–253N) 6 weeks post intervention. The athlete returned to full training (volume and intensity) pain free and international level competition at 4 months post ATI. Conclusion: An athlete who had previously undergone unsuccessful conservative management demonstrated significant improvement in function and in tendon morphology post intervention.